Pengaplikasian Media Dalam Pembelajaran Bahasa Arab Pada Peserta Didik MTS. Assalam Plered - H, Herawati; Zufa, Zuhrotul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Arabic language learning in this study aims to see the learning process using youtube media at Madrasah Tsanawiyah Assalam and find out its advantages and disadvantages. This research is a descriptive research using a qualitative approach. Data was collected using observation, and interviews. The object of the research is a 7th grade student. After this research was carried out, it was shown that the videos on youtube can be used as an interesting learning medium in learning Arabic. But of course there are advantages, for example, ease of access and disadvantages in this media are the limitations of facilities.